New York Paper - A Study of Certain Alloys of the Lead-tin-cadmium System with Reference to Their Use as Solders (with Discussion) - Carl E. Swartz (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
Although a number of articles appeared during the war advocating the use of cadmium in lead-tin solders, very little information of value can be found in the literature regarding the properties of solders containing cadmium. In most of the published articles the cadmium seems to have been considered merely as a partial substitute for tin in a tin-lead alloy rather than as an essential constituent of a ternary alloy. The primary object of the substitution of cadmium for tin was to lessen the amount of tin required, at a time when the latter was scarce and high-priced, and thus to produce a cheaper solder. While this object was accomplished, the new properties resulting from a change from a binary lead-tin alloy to a ternary lead-tin-cadmium alloy were not given proper consideration in many cases. For the past few years, the American Smelting & Refining Co. has been marketing a very considerable amount of cadmium in the form of lead-tin-cadmium alloys for use as solders for certain special purposes, and the successful use of these solders suggested that if more extensive knowledge were available concerning the properties of lead-tin-cadmium alloys of various compositions their field of usefulness might be materially extended. The investigation described in the present paper was undertaken to obtain this information and, by means of tests under conditions approaching those of practical use, to determine the suitability of cadmium solders for various purposes. Characteristics and Requirements of Solders in General General Physical Properties.—When cast into bars, solder should present a smooth and bright appearance free from oxide inclusions and bubbles. Ductility should be as great as possible without sacrificing tensile strength, and vice versa. Hardness and specific gravity are not of any great importance. Melting Characteristics.—The melting or solidification range is important. This statement applies both to the extent of the range and to the actual temperature at which complete solidification occurs. A rather narrow solidification range is desirable in soft solders in order that solidification may take place quickly. The solder should have high fluidity at temperatures only slightly above its melting range. For a